1983
DOI: 10.1128/iai.42.2.558-566.1983
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo complementation of Streptococcus mutans mutants defective in adherence

Abstract: Previous studies have shown that adherence-defective mutants of Streptococcus mutans PS14, serotype c, can be grouped into several different phenotypic groups. In this study a method was developed to test for complementation between pairs of nonadhering mutants which possess different genotypic defects. Mutant strains UAB95 and a spectinomycin-resistant derivative of UAB95 (UAB516) were found to exhibit increased levels of adherence when grown together with UAB230 in media containing sucrose as compared to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 31 publications
(38 reference statements)
0
18
0
Order By: Relevance
“…Dex also possesses an N-terminal signal peptide and a C-terminal sorting signal in VRs (15,18,35). In addition, Dex is thought to be responsible both for controling the amount and nature of extracellular glucans and for utilizing extracellular glucans as a carbohydrate source (5,21,25,28,34). Consequently, Dex is thought to be one of the virulent factors in mutans streptococci.In this paper we sequenced and characterized the dex gene of S. rattus ATCC19645 and compared the Dex molecule of S. rattus with that of S. mutans, S. sobrinus, Streptococcus downei, and Streptococcus salivarius.…”
mentioning
confidence: 99%
“…Dex also possesses an N-terminal signal peptide and a C-terminal sorting signal in VRs (15,18,35). In addition, Dex is thought to be responsible both for controling the amount and nature of extracellular glucans and for utilizing extracellular glucans as a carbohydrate source (5,21,25,28,34). Consequently, Dex is thought to be one of the virulent factors in mutans streptococci.In this paper we sequenced and characterized the dex gene of S. rattus ATCC19645 and compared the Dex molecule of S. rattus with that of S. mutans, S. sobrinus, Streptococcus downei, and Streptococcus salivarius.…”
mentioning
confidence: 99%
“…So far, the dextranases of Streptococcus mutans and Streptococcus sobrinus were well characterized by enzyme purification and gene cloning (2,(14)(15)(16)38). Previous studies suggested important roles of Dex in plaque formation: one was that Dex supplies carbohydrate nutrients through the degradation of glucan (5,14,24) and the other was that Dex modifies the glucan substrate to a more firm and adhesive form (5,21,28,37). Consequently, Dex is thought to be one of the virulent factors in mutans streptococci.…”
mentioning
confidence: 99%
“…We divided these mutants into at least 13 phenotypic groups based on phenotypic traits (27). Mixed cultivation in sucrose-containing medium of two nonadhering mutants of differing phenotypic traits (UAB95 and UAB230) allowed complementation for adherence, and these mutants complemented each other for caries production in gnotobiotic rats as well (24).…”
mentioning
confidence: 99%
“…One unexpected observation from in vitro complementation studies was that several mutants, namely UAB108, UAB113, UAB124, and UAB244, inhibited the adherence of both mutant and wild-type control strains (24). These mutants fall into the same phenotypic group (27).…”
mentioning
confidence: 99%